Ultrasonography Assessment of Neck Anatomy for Prediction of Difficult Mask Ventilation in Obese Patients: A Prospective Observational Study - Ignatius Wong Hsun-Hong; Azarinah Izaham; Syarifah Noor Nazihah Sayed Masri; Muhammad Maaya; Siti Nidzwani Mohamad Mahdi; Khazrul Nizar Abd Kader; Maryam Budiman; Yazmin Yaacob (Diagnostics)
Background: Effective mask ventilation is a very important aspect of ensuring adequate oxygenation and ventilation. However, predicting difficult mask ventilation (DMV) using bedside clinical tests remains challenging due to poor sensitivity. Our objective was to determine the correlation between the preoperative ultrasonography of anterior neck anatomy and difficult mask ventilation in different obesity classes. Methods: A prospective, observational study enrolled 90 adult obese patients undergoing general anesthesia from December 2020 to November 2021 (30 patients for each class of obesity). Ultrasonography measurements were recorded for the distance of skin (DS) to hyoid bone (DSHB), epiglottis (DSEM), the anterior commissure of the vocal cords (DSAC), thyroid isthmus (DSTI), and trachea at jugular notch (DSTJ). The difficulty of bag mask ventilation was graded using the Han scale. The Kendall Tau correlation coefficient was used to correlate the different ultrasonography parameters to DMV. Receiver-operating characteristic (ROC) curves were used to determine the sensitivity and specificity of the measured ultrasonography distances, and the Youden index was used to calculate the optimal cut-off values. Results: Results revealed twenty patients (22.2%) were categorized as having difficult mask ventilation. There was a statistically significant increase (p = 0.011) in the number of patients with Mallampati II in class III obesity compared to class I obesity. DSHB showed a statistically significant and strong correlation with difficult mask ventilation in patients with class II (p = 0.002, r = 0.464) and class III obesity (p = 0.002, r = 0.475). A DSHB cut-off value of 1.35 cm has a sensitivity of 83.3% and specificity of 78.8% for class III obesity. Similarly, a DSTJ cut-off value of 1.13 cm has a sensitivity of 83.3% and specificity of 66.7% for class III obesity. Conclusions: Notably, DSHB was the most specific parameter and equally as sensitive as DSTJ in predicting difficult mask ventilation in morbidly obese patients.